Tafamidis in Transthyretin Amyloid Cardiomyopathy. (May 2015) - Maurer, Mathew S.; Grogan, Donna R.; Judge, Daniel P.; Mundayat, Rajiv; Packman, Jeff; Lombardo, Ilise; Quyyumi, Arshed A.; Aarts, Janske; Falk, Rodney H.
<x xml:space="preserve">Abstract</x> Background— Transthyretin (TTR) amyloidosis is a progressive systemic disorder caused by misfolded TTR monomers that cumulatively deposit in the heart and systemically as amyloid. Methods and Results— This phase 2 open-label trial evaluated the stabilization of TTR tetramers using 20 mg of tafamidis daily at week 6 (primary end point), month 6, and month 12, as well as safety of tafamidis treatment and efficacy with respect to progression of TTR amyloid cardiomyopathy. Thirty-one wild-type patients (median age, 76.7 years; 93.5% men) with a median disease duration of 55.6 months and mild to moderate heart failure (96.8%; New York Heart Association, classes I–II) were enrolled. Thirty of 31 patients (96.8%) achieved TTR stabilization after 6 weeks and 25 of 28 patients (89.3%) after 12 months. After 12 months of treatment, 3 patients discontinued prematurely, 2 patients died, 7 patients were hospitalized because of cardiovascular events, 20 of 28 patients demonstrated preserved New York Heart Association classification status, but 15 of 31 (48.4%) patients had clinical progression (eg, admission for cardiac failure, atrial fibrillation, and syncope). N-terminal prohormone brain natriuretic peptide levels did not increase significantly over time, troponin I and troponin T increased moderately, and no consistent clinically relevant changes were seen in echocardiographic cardiac assessments. Tafamidis treatment was generally well tolerated although 7 of 31 patients had bouts of diarrhea. Conclusions— Tafamidis treatment effectively achieved and maintained TTR stabilization and was well tolerated. The absence of significant changes in most biochemical and echocardiographic parameters suggests that further evaluation of tafamidis in TTR amyloid cardiomyopathy is warranted. Clinical Trial Registration— URL: http://www.clinicaltrials.gov. Unique identifier: NCT00694161.